Status of shallow reefs around Apid Island, Inopacan, Leyte, Philippines - Benliro, I.M.P; Bothe, C.I.I; Sonder, K.; Szinicz, G.; Cesar, S.A.; Schoppe, S. (Annals of Tropical Research, 1999)
A rapid coral reef survey was conducted along selected sites in Apid and Digyo Islands on Aug. 30-31, 1999. Transect lines (20 meter) were laid in different sites in the reefs. The assessment revealed that the entire reef area is in a critical status. The combined effects of previous destructive fishing practices, over.exploitation, El Niño phenomenon and a Crown-of-Thorns seastar population outbreak resulted in severe damage to the reef. Dead corals were ubiquitous. Marine resources inside the protected marine sanctuary were higher and in better condition compared to areas which were open for exploitation. Ecological awareness was indicated by the absence of any trash in the reefs and the continuing effort of the community to maintain the marine sanctuary.